Building and Strengthening Communities Through Culturally Responsive Inter-Agency Collaboration in Southern New Jersey - Carla Villacis; Samuel Ross (Journal of Community Engagement and Scholarship)
Organizations working with immigrant families navigate circumstances related to families’ cultural background, personal resources, and social connections by engaging in culturally responsive practices. Immigrant families experience linguistic, cultural, and policy challenges in search for resources available to them in the United States, often through minimal social connections (Furman et al., 2009; Suárez-Orozco et al., 2012). Inter-agency collaborations help immigrant families navigate these barriers (Vanek et al., 2020) by coordinating programming and case management to streamline the support available to families. This study documents the challenges and social-delivery practices that immigrant Hispanic families and agency collaborators must navigate in the Southern New Jersey region. Through interviews with 15 agency staff members and 21 Hispanic immigrant families these agencies served, researchers gathered insights into service providers’ reflections on their work and families’ perspectives on the assistance they received. Family caregivers spoke candidly about their struggles to find employment, childcare, and other services in Spanish, learn English, and balance family obligations in the U.S. and in their home countries. In turn, agency staff shared their experiences with prejudice from locals towards immigrants, on leveraging formal and informal resources to assist their families, and on identifying funding sources that do not require their clients’ immigration status. Interviews also revealed that participants’ ability to rely on each other as families, providers, and communities bolstered a sense of support and community engagement.